Effect of zinc oxide on performance of ultrafiltration membrane for humic acid separation - Yunos, Muhamad Zaini (Universiti Teknologi Malaysia, 2013)
The effects of different zinc oxide concentration on morphology, contact angle, surface roughness and rejection towards humic acid in polysulfone membrane were investigated. Flatsheet ultrafiltration membrane were prepared by using polysulfone as based polymer, polyethylene glycol as pore forming agent, zinc oxide as manipulated additive and TAP as compatibilizer. In this study, N, methyl-2-pyrrolidone were used as solvent and water as non solvent. The membrane were prepared via phase inversion method. Results showed that pure water flux was enhanced by the presence of zinc oxide up to 1 wt% and tend to decrease beyond this concentration. The increased pure water flux was attributed to the increase in hydrophilicity and surface roughness of membrane according to contact angle and AFM measurement. The rejection test with humic acid as solute revealed that by increasing zinc oxide concentration, rejection increases up to 98% at 2 wt% of zinc oxide. Therefore polysulfone/zinc oxide in this study can provide potential application for river water treatment which consist high humic acid concentration.